Phytochemical Analysis And Antimicrobial Properties Of Selected Medicinal Plants Against Bacteria Associated With Diabetic Patients - KAVISHANKAR G.B; LAKSHMIDEVI N; MAHADEVA MURTHY S (International Journal of Pharma and Bio Sciences, 2011)
The antibacterial activity of ten medicinal plants was screened for different bacterial strains using methanol and water as solvents. The leaves of seven plants (Emblicaofficinalis, Achyranthesaspera, Coleus aromaticus, Acacia nilotica, Solanumnigrum, Azardirachtaindica, Prosopisspicigera) and the bark of three plants(Syzygiumcumini, Mangiferaindica, Lawsoniainermis)were dried and powdered before being subjected to soxhlation. All extracts were concentrated by using rotary flash evaporator. The phytochemical screening was carried out to know the compounds responsible for these activities. Methanol and water extracts were tested against Escherichia coli, Staphylococcus aureus, Enterobacteraerogenesand Pseudomonas aeruginosa. The antibacterial assays in this study were performed by the agar-well diffusion methods so that they could be quantified by measuring the zones of growth inhibition diameters, MIC values. The susceptibility of the bacteria to the crude extracts on the basis of zones of growth inhibition varied according to microorganism and extracting solvent. In most of the above mentioned plants, the methanol extract produced the highest activity when compared to aqueous extract. The organisms used for the purpose of this investigation were associated with opportunistic infections in diabetic patients.On the basis of the results obtained, it could be concluded that methanol could be used for extracting antimicrobial compounds from both leaves and bark. The present study showed that the plant extracts possessed the antimicrobial activity against some organisms associated with diabetes